(untitled) (Eurasian Scientific Herald, 2022)
This paper aims to investigate and compare data about Charlotte Bronte. Initially, it presents some specific information about the life and literary works of the author. Secondly, it draws the reader’s attention to the personality of the writer by depicting her internal and external appearance. Finally, the article reveals some fragments from the author’s novel “The Professor” and intends to decode the literary and actual messages of the work.